Anticuerpos Anti-tiroperoxidasa en mujeres diagnosticadas con Hipotiroidismo. - Pérez Olivo, Nayeli Esthefania (2024)
ABSTRACT: Hashimoto’s thyroiditis is a common cause of autoimmune hypothyroidism, where the detection of antithyroperoxidase antibodies (ATPO) is fundamental for analyzing this condition. This study aimed to investigate serum ATPO levels, which serve as a diagnostic tool for the early detection of hypothyroidism in women. A review of bibliographic references was conducted to contribute to a better understanding, development of effective determination strategies, and treatment for this patient group. The study was descriptive, documentary, non-experimental, and retrospective, reviewing 30 scientific articles, of which 22 were selected based on inclusion and exclusion criteria. Information was sourced from major databases such as PubMed, Elsevier, Scielo, Medigraphyc, Redalyc, ProQuest, and institutional repositories. Evidence highlighted that the electrochemiluminescence technique stands out for its high sensitivity in detecting anti-thyroperoxidase antibodies. The ATPO test is crucial for the early identification of hypothyroidism, which predominantly occurs in women, representing 46.15%. Finally, the accurate interpretation of ATPO values obtained from studies reveals a deeper understanding of the disorder’s severity, guiding effective disease management and contributing to the optimization of healthcare in the field of autoimmune thyroid